A review and meta‐analysis of the effects of climate change on Holarctic mountain and upland bird populations - Scridel, Davide; Brambilla, Mattia; Martin, Kathy; Lehikoinen, Aleksi; Iemma, Aaron; Matteo, Anderle; Jähnig, Susanne; Caprio, Enrico; Bogliani, Giuseppe; Pedrini, Paolo; Rolando, Antonio; Arlettaz, Raphaël; et al. (Ibis (London, England), 2018)
Mountain regions are globally important areas for biodiversity but are subject to multiple human‐induced threats, including climate change, which has been more severe at higher elevations. We reviewed evidence for impacts of climate change on Holarctic mountain bird populations in terms of physiology, phenology, trophic interactions, demography and observed and projected distribution shifts, including effects of other factors that interact with climate change. We developed an objective classification of high‐elevation, mountain specialist and generalist species, based on the proportion of their breeding range occurring in mountain regions. Our review found evidence of responses of mountain bird populations to climate (extreme weather events, temperature, rainfall and snow) and environmental (i.e. land use) change, but we know little about either the underlying mechanisms or the synergistic effects of climate and land use. Long‐term studies assessing reproductive success or survival of mountain birds in relation to climate change were rare. Few studies have considered shifts in elevational distribution over time and a meta‐analysis did not find a consistent direction in elevation change. A meta‐analysis carried out on future projections of distribution shifts suggested that birds whose breeding distributions are largely restricted to mountains are likely to be more negatively impacted than other species. Adaptation responses to climate change rely mostly on managing and extending current protected areas for both species already present, and for expected colonizing species that are losing habitat and climate space at lower elevation. However, developing effective management actions requires an improvement in the current knowledge of mountain species ecology, in the quality of climate data and in understanding the role of interacting factors. Furthermore, the evidence was mostly based on widespread species rather than mountain specialists. Scientists should provide valuable tools to assess the status of mountain birds, for example through the development of a mountain bird population index, and policy‐makers should influence legislation to develop efficient agri‐environment schemes and forestry practices for mountain birds, as well as to regulate leisure activities at higher elevations.